Irreducibility on monotonically normal spaces and GO-spaces - Hirata, Yasushi; Yajima, Yukinobu (Topology Proceedings, 2025)
We first present a characterization for the irreducibility of monotonically normal spaces. Making use of it, we proceed another characterization for the irreducibility of GO-spaces. Next, we discuss when GO-spaces have an irreducible subspace which is not $D$. As a result, we give a characterization for GO-spaces which have a closed irreducible subspace being not $D$.